How does Religious Organizations interpret Public Service Ethics? - Moner, Yasmira Paute; Tomaro, Queenie Pearl V (Universitas Muhammadiyah Yogyakarta, 2018)
Virtue ethics indicating that good actions are indicative of attempts to develop processes (thinking and behaviour) that emanate from oneâ€™s character and guide one to right action (Eagan, 2016). This virtues are oftentimes embedded in religious institutions, such that Shariâ€™ah (Islamic Law) is Islamic ethics. Having a virtous character according to this philosophical tradition must be possessed by public servants to build a state of just and developed society. Hence, this paper is a cursory guide to look into the basic role of the Chatholic Church andÂ Muhammadiyah in influencing the organizational culture of the communities they are serving. the common teachings of Islam and Catholicism, in the context of public ethics service is one that is upholding the moral virtues of good governance, which is deontological in nature and consequential in effect.